PENGARUH INTEGRITAS, KEAHLIAN AUDIT, KOMPETENSI, DAN INDEPENDENSI TERHADAP KUALITAS AUDIT (Studi Empiris Pada Kantor Akuntan Publik Di Pekanbaru, Padang, dan Batam) - Putri Rachmiaty; Kirmizi '; Azhari ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of integrity, audit expertise, competency, and independency, positive effect on audit quality. In this study, researchers examined the quality of audits in Public Accounting Firm (KAP) in the city of Pekanbaru, Padang, Batam and using independent variable , namely integrity, audit expertises, competency, and independency.The population in this study were all auditors working at the firm in the city of Pekanbaru , Padang, and Batam. Sampling was done by using purposive sampling method, and the total sample of 70 respondents. The primary data collection method used was a questionnaire method. The data analysis technique used in this study is multiple regression analysis techniques.The results of testing the hypothesis in this study indicate that the integrity, audit expertise, and the independency of positive and significant impact on audit quality. While the competency variable had no significant effect on audit quality significant level of α < 0,05. Simultaneously, all independent variables are positive and significant impact on audit quality significant level of α < 0,05.The degree of influence the value of (R2) by all independent variables are 46,8% and 53.2% influenced by other variables.Keywords : independency, competency, audit expertise, integrity, audit quality.